2016
DOI: 10.1109/access.2016.2628440
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on Networked Music Performance Technologies

Abstract: Networked music performance (NMP) is a potential game changer among Internet applications, as it aims at revolutionizing the traditional concept of musical interaction by enabling remote musicians to interact and perform together through a telecommunication network. Ensuring realistic performance conditions, however, constitutes a significant engineering challenge due to the extremely strict requirements in terms of network delay and audio quality, which are needed to maintain a stable tempo, a satisfying sync… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 66 publications
1
109
0
3
Order By: Relevance
“…Since the advent of the internet, thorough research has been undertaken in the realm of remote Networked Musical Performances (NMP) [30]. Today however, local NMPs still seem today more viable, both technically and artistically speaking.…”
Section: Networked Musical Performances -Nmpsmentioning
confidence: 99%
“…Since the advent of the internet, thorough research has been undertaken in the realm of remote Networked Musical Performances (NMP) [30]. Today however, local NMPs still seem today more viable, both technically and artistically speaking.…”
Section: Networked Musical Performances -Nmpsmentioning
confidence: 99%
“…where d mouthtoear denotes the mouth to ear latency (or Over‐all One‐way Source‐to‐Ear (OOSE) delay), d soundtrans is the delay inserted by the transmitter's sound‐card, d network is the delay added due to the streaming process through the network, and dsoundrec is the delay inserted by the receiver's sound‐card. d proctrans and d procrec describe the delay inserted due to the audio processing and the encoding/decoding in the transmitter/receiver side.…”
Section: Prerequisitesmentioning
confidence: 99%
“…d proctrans and d procrec describe the delay inserted due to the audio processing and the encoding/decoding in the transmitter/receiver side. In more detail, the end‐to‐end delay in NMP systems involves many factors that affect it . These factors are: the propagation delay for the sound in the air between the audio source and the microphone, the transformation process from sonic wave to electric signal via the microphone, the audio signal transmission via the microphone to the transmitter computer, the analog to digital conversion, combined with additional encoding process, in the transmitter's sound‐card using drivers, the preparation stage for the audio packetization before the transmission via the Internet, the propagation delay using the Internet (network delay), the depacketization and decoding process in the receiver side, the application buffering process in the receiver side, the driver buffering using the receiver's sound‐card and the digital to analog conversion process, the signal transmission using the audio output connector, the transformation process from electrical signal to sonic wave using the audio output devices, such as headphones or loudspeakers, the propagation delay via the loudspeakers in the air to the receiver's ear. …”
Section: Prerequisitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The eects of latency and jitter have been studied and surveyed for the past focusing mainly on perceived synchronization and they present parameters to bear in mind while proposing musical interactions. In these works, authors demonstrated that human perception is constrained by some limits of rhythm, haptics, and other limitations discovered and evaluated through many careful experiments, whereby latencies up to 30 ms are acceptable for multimedia applications, but higher latencies may aect interaction (Lago and Kon , 2004;Rottondi et al , 2016;Schuett , 2002).…”
Section: Research Descriptionmentioning
confidence: 99%